Pengaruh Variasi Campuran Aspal Plastik terhadap Daya Tahan Jalan Raya di Iklim Tropis di Daerah Lombok Tengah - Ahmad Firdaus (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The use of plastic waste in road construction has emerged as an innovative solution to address both infrastructure durability and environmental sustainability. This study aims to investigate the effect of plastic-modified asphalt mixtures on the durability of road pavements in tropical climates, particularly in Central Lombok. The research adopts an experimental method using various proportions of polyethylene plastic waste (2%, 4%, and 6% by weight of bitumen) in asphalt mixtures. Samples were tested for stability, flow, and resistance to moisture damage using the Marshall test. The results show that the 4% plastic-modified asphalt mixture exhibits optimal performance in terms of load resistance and moisture susceptibility. The findings suggest that plastic waste integration not only improves asphalt pavement performance but also supports local waste management initiatives. This study contributes to sustainable road construction practices in tropical regions and highlights the potential of plastic waste reuse in infrastructure development.